A Full Employment, Keynesian Theory of International Trade - Collery, Arnold (Quarterly Journal of Economics, 1963)
Introduction, 438. — A full employment, Keynesian theory of a closed economy, 438. — The model with trade between two countries, 443. — The money markets: freely flexible exchange rates, 447; the international gold standard, 449, stability, 451. — Theory of tariffs, 452. — The transfer problem: financial transfer, 455; transfers that affect consumption, 457.